Musik Rodat Sebagai Sumber Belajar Musik Daerah Setempat di Prodi Pendidikan Seni Pertunjukan Universitas PGRI Palembang - Rio Eka Putra; Sonia Anisa Utami (Faculty of Languages and Arts, Universitas Negeri Padang, 2023)
The development of education with interest in practical lectures today has experienced a slight decline when seen in terms of students' interest in traditional music, especially regional music courses in the Performing Arts Study Program at PGRI University in Palembang. In this case, the researcher as a lecturer hopes to stimulate students' interest in being more creative and understanding theory and practice in learning local regional music. The research aims to provide students with an understanding of the history of Rodat's musical development and to be able to play one of his repertoires entitled Bissahri Robbi through notation quickly and precisely. Data collection techniques were carried out using observation, interviews and documentation steps. The data that has been collected is then presented descriptively. The results of the research show that learning Rodat music can help students understand history, instrument techniques, musical aspects, text aspects (lyrics), as well as the form of presentation of Rodat music to the community as a source of learning regional music. Perkembangan pendidikan dengan minat perkuliahan praktek dewasa ini mengalami penurunan apabila dilihat dari segi peminatan mahasiswa terhadap musik tradisional, khususnya mata kuliah musik daerah pada Prodi Seni Pertunjukan di Universitas PGRI Palembang. Dalam hal ini peneliti sebagai dosen berkeinginan agar dapat memacu minat mahasiswa untuk lebih kreatif serta memahami teori dan praktek, dalam pembelajaran musik daerah setempat. Penelitian bertujuan untuk memberikan pemahaman kepada mahasiswa mengenai sejarah musik Rodat serta mampu memainkan salah satu repertoarnya dengan judul Bissahri Robbi melalui notasi dengan cepat dan tepat. Teknik pengumpulan data dilakukan dengan langkah observasi, wawancara, serta dokumentasi. Data yang sudah dikumpulkan selanjutnya disajikan secara deskriptif. Hasil penelitian menunjukkan bahwa pembelajaran musik Rodat dapat membantu mahasiswa dalam memahami sejarah, teknik instrument, aspek musikal, aspek teks (lirik), serta bentuk penyajian musik Rodat pada masyarakat sebagai sumber belajar musik daerah.